The Role of Government Institutions in Rehabilitation of Handling Victims of Narcotic Abuse - Enggartiasto Adipradana; Suwari Akhmaddhian; Diding Rahmat; Yunusrul Zen (Universitas Kuningan, 2020)
The purpose of this study is to find out the regulations of rehabilitation for victims of narcotics abuse carried out by rehabilitation institutions as well as to analyze the role of Rehabilitation Institution in handling victims of narcotics abuse in Kuningan District. This study employed an evaluative method of analysis which is a method of collecting and presenting data to analyze actual situation and then rational analysis was carried out based on juridical references through library research and field research. The results indicated that the rehabilitation is regulated in Law No. 35 of 2009 concerning Narcotics, Government Regulation No. 25 of 2011 concerning Implementation of Mandatory Self-Reporting of Narcotics Addicts, Regulation of the Minister of Social Affairs of the Republic of Indonesia No. 08 of 2014 concerning Guidelines for Social Rehabilitation of Narcotics Addicts and Victims of Narcotics Abuse Confronting the Law in Social Rehabilitation Institutions, and Regulation of the Minister of Social Affairs of the Republic of Indonesia No. 03 of 2012 concerning the Standard of Social Rehabilitation Institutions for Victims of Narcotics, Psychotropic, and other Addictive Substances. Meanwhile, the role of rehabilitation institution, such as Mandatory Report Recipient Institution (IPWL), is to carry out social rehabilitation programs for victims of narcotics abuse by applying therapeutic community and counseling methods. Peran Lembaga Pemerintah dalam Rehabilitasi Penanganan Korban Penyalahgunaan NarkotikaTujuan penelitian ini adalah untuk mengetahui bagaimana pengaturan rehabilitasi bagi para korban penyalahgunaan narkotika oleh lembaga rehabilitasi dan untuk menganalisis bagaimana peran Lembaga Rehabilitasi dalam penanganan korban penyalahgunaan Narkotika di Kabupaten Kuningan. Metode penelitian yang digunakan oleh peneliti dalam pembahasan penelitian ini adalah metode evaluatif analisis, yaitu suatu metode mengumpulkan dan menyajikan data yang diperoleh untuk menganalisis keadaan yang sebenarnya dan selanjutnya dilakukan analisa rasional berdasarkan acuan yuridis melalui penelitian kepustakaan dan penelitian lapangan. Hasil penelitian yaitu bahwa pengaturan mengenai rehabiliasu diatur dalam Undang-Undang No 35 Tahun 2009 Tentang Narkotika, Peraturan Pemerintah No 25 Tahun 2011 Tentang Pelaksanaan Wajib Lapor Pecandu Narkotika, Peraturan Menteri Sosial Republik Indonesia Nomor 08 Tahun 2014 Tentang Pedoman Rehabilitasi Sosial Pecandu Narkotika Dan Korban Penyalahgunaan Narkotika Yang Berhadapan Dengan Hukum Di Dalam Lembaga Rehabilitasi Sosial, Peraturan Menteri Sosial Republik Indonesia Nomor 03 Tahun 2012 Tentang Standar Lembaga Rehabilitasi Sosial Korban Penyalahgunaan Narkotika, Psikotropika, Dan Zat Adiktif Lainnya. Peran lembaga rehabilitasi sebagai Institusi Penerima Wajib Lapor (IPWL) adalah melaksanakan program rehabilitasi sosial bagi korban penyalahgunaan narkotika dengan menggunakan metode terapi komunitas, dan konseling.